Cardiopulmonary bypass - Ghosh, Sunit; Falter, Florian; Perrino, Jr, Albert C. (Cambridge : Cambridge University Press, 2015)
Cardiopulmonary Bypass, 2nd edition, offers a complete introduction to this specialist technique for medical and technical personnel involved in extracorporeal cardiopulmonary support. A clinically based overview of the subject is provided and updated chapters incorporate the most current developments in the field. Introductory chapters cover equipment and preparation of the cardiopulmonary bypass machine, safety and monitoring, routine conduct of bypass, and the process of weaning from mechanical to physiological circulation. Specialist chapters on mechanical support, ECMO, special surgical procedures, blood conservation techniques, and particular medical conditions that affect the conduct of cardiopulmonary bypass are also included. This new edition includes self-assessment multiple choice questions at the end of each chapter, allowing readers to test their own understanding of the material. Written and edited by specialists from leading cardiac centres in the UK and USA, this is an invaluable resource for clinical perfusion scientists, cardiac surgeons and cardiothoracic anaesthetists in training.
Title from publisher's bibliographic system (viewed on 13 May 2016).